Materializing the Digital: Architecture as Interface - Shelby Elizabeth Doyle (Materia Arquitectura)
Digital technologies have reshaped our experience of the material world. In this augmented and hybridized condition, information (and architecture) has no social relevance unless circulated, shared, and integrated into everyday life through interfaces between the digital and physical. The ‘more serious work’ presented here is digital craft as a method for materializing the digital and extending the agency of computational thinking and parametric design into a new social project for architecture. In an age of digital social networks, the future of public spaces will largely depend on an architecture that navigates the interface between the material and the digital.